Effects of dynamic deformation of Fermi surface on giant resonances in nuclei - V. I. Abrosimov; O. I. Davydovska (Ядерна фізика та енергетика, 2025)
The nature of dynamic changes in the momentum-space distribution of nucleons (dynamic deformation of the Fermi surface) associated with monopole and quadrupole giant resonances in spherical nuclei has been studied. Within the kinetic model for collective excitations in nuclei, the momentum flux tensor associated with these resonances has been considered, which contains information about dynamic changes of the Fermi surface during a collective excitation in the nucleus. It was found that the ratio of the normal component of the momentum flux tensor to the variation of the nucleon density, associated with monopole resonance, has a hydrodynamic character inside the nucleus: it is approximately equal to the compressibility coefficient of the nuclear Fermi liquid. While this relation has a different character for quadrupole resonance: its local values differ significantly from the compressibility coefficient. It is found that the off-diagonal component of the momentum flux tensor for the monopole resonance is zero, while the off-diagonal component of the momentum flux tensor associated with the quadrupole resonance has a significant magnitude, which explicitly reveals the influence of the dynamic deformation of the Fermi surface on the formation of this resonance.